AT 2017fvz: a nova in the dwarf irregular galaxy NGC 6822. Issue 3 (18th April 2019) - Healy, M W; Darnley, M J; Copperwheat, C M; Filippenko, A V; Henze, M; Hestenes, J C; James, P A; Page, K L; Williams, S C; Zheng, W
ABSTRACT: A transient in the Local Group dwarf irregular galaxy NGC 6822 (Barnard's Galaxy) was discovered on 2017 August 2 and is only the second classical nova discovered in that galaxy. We conducted optical, near-ultraviolet, and X-ray follow-up observations of the eruption, the results of which we present here. This 'very fast' nova had a peak V -band magnitude in the range −7.41 > MV > −8.33 mag, with decline times of t 2, V  = 8.1 ± 0.2 d and t 3, V  = 15.2 ± 0.3 d. The early- and late-time spectra are consistent with an Fe ii spectral class. The H α emission line initially has a full width at half-maximum intensity of ∼2400 km s −1 – a moderately fast ejecta velocity for the class. The H α line then narrows monotonically to ∼1800 km s −1 by 70 d post-eruption. The lack of a pre-eruption coincident source in archival Hubble Space Telescope imaging implies that the donor is a main-sequence, or possibly subgiant, star. The relatively low-peak luminosity and rapid decline hint that AT 2017fvz may be a 'faint and fast' nova.